Hybrid Treatment of Tannery Effluent by Natural Coagulants for Vegetative Seed Germination - Al Mamun, Md Abdulla; Lamia, Quazi Farjana (Journal of Engineering Science, 2022)
Treatment of the tannery wastewater by mixing the effluents in desired ratio, with natural coagulants prepared by using natural elements and small quantity of chemicals is a cost-effective method. Here, indigenous naturalcoagulant named chitosan extracted from shrimp-shell and Morinaga Oleifera seed as a bio-absorbent was used. To the best of knowledge, this comprehensive hybrid method not been investigated yet for tannery effluent treatment. Chitosan can also be used in water processing engineering as a part of a filtration process. Chitosan causes the fine sediment particles to bind together and is subsequently removed with the sediment during sand filtration. The Chitosan and Morinaga seeds extraction works on wastewater treatment in an excellent way. The reduction of BOD, COD, Salinity proves the effectively of these prepared coagulants from natural elements. Resultant coagulant treated wastewater significantly reduced the pollutants were 97% TDS, 46% COD, 10% Salinity and 43% BOD respectively and removal proves the effectivity of these prepared coagulants. Moreover, it will help on the designing a low-cost chemical free treatment technology of the tannery effluent as for attracting the tannery-owner to set up a treatment plant. At the same time, the effect of the treated water to the vegetative seed germination and growth was also examined. That can be identified the impact of application of the treated wastewater for irrigation. Journal of Engineering Science 13(1), 2022, 73-79